Arsenic in Rice Agro-Ecosystem: Solutions for Safe and Sustainable Rice Production - Munish Kumar Upadhyay (Frontiers in Sustainable Food Systems, 2020)
Arsenic (As) is a toxic metalloid classified as group 1 carcinogen. The presence of As in high concentrations in paddy soil and irrigation water results into high As accumulation in rice grains posing a threat to the health of millions of people worldwide. The main reason for As contamination is the biogeochemical weathering of rocks and the release of bound As into groundwater. Human interventions through intensive agricultural practices and excessive groundwater consumption have contributed greatly to the prevailing As contamination. The flooded cultivation practice of rice favors the accumulation of As in rice grains. The formation of iron (Fe) plaque on paddy root surfaces, changes in the level of Fe and manganese (Mn) hydro(oxides), soil organic matter, soil pH, soil redox potential, and microbial activities under flooding conditions influence concentrations of various As species in the water–soil–paddy agroecosystem and favor the predominance of highly mobile arsenite [As(III)]. Once inside the rice plant, the concentration of As is regulated by arsenate reduction, arsenite efflux, root-to-shoot translocation, and vacuolar sequestration of As. The detailed understanding gained about the factors affecting As dynamics in soil and transport in rice plants may be helpful in developing feasible methods for sustainable cultivation of rice plants with low grain As. There is also need to ensure high production yields as well as grain quality to achieve the goals of sustainable development. This article discusses the aspects of As in the water–soil–paddy agroecosystem and presents suitable strategies to reduce the As load in rice grains.